Price Shocks, News Disclosures, and Asymmetric Drifts - Lu, Hai; Wang, Kevin Q.; Wang, Xiaolu (The Accounting Review, 2014)
ABSTRACT Motivated by investor disagreement and corporate disclosure literatures, we examine how stock price shocks affect future stock returns. We find that both large short-term price drops and hikes are followed by negative abnormal returns over the subsequent year, consistent with the conjecture that price shocks are useful indicators of intertemporal spikes in investor disagreement and investor opinion converges gradually. The asymmetric drifts involve return continuation for negative price shocks versus return reversal for positive price shocks, and are in sharp contrast to the general findings of symmetric drifts in corporate event studies. Moreover, price shocks associated with public news events are followed by significantly weaker downward drifts, suggesting that news disclosures mitigate disagreement-induced overpricing. Examining the dynamics of a disagreement proxy during and after price shocks, we provide further evidence for the disagreement hypothesis. The economic significance of the price shock effect is illustrated with a revised momentum strategy that generates an annualized abnormal return of 16.92 percent.